Strength of the Bond of Structural Steel S235JR to Bronze SAE660 Produced by Casting in Pre-Mold - Zaheri M.; Vahdat S.E. (Archives of Foundry Engineering, 2017)
Different methods are used for production of bronze bearings. In terms of technical specifications, the success of each of these methods depends on the bond’s strength and in terms of economic, the production method is important. In this study, the aim is to study the strength and microstructure of steel-bronze thrust bearing bond that has been produced through the casting using pre-mold. In this study, in order to bond, the raw metals are chemically washed with sulfuric acid solution for five minutes at first. Then, the molten bronze SAE660 is cast in a structural steel S235JR pre-mold. The bond’s strength has been measured using the shear test three times; the measurement of bond’s length has been done using field emission scanning electron microscope (FESEM). The results indicate that the strength of the bond is at least 94.8 MPa and bond’s length is 0.45 micrometers. Therefore, this method was successful for trust bearing application.